PT. Indofood Sukses Makmur Tbk Strategies for more International growth & Global Competition. - Abdulrahman Khaled Ba Wazir; Daisy Mui Hung Kee; Aric Farrel Gunawan Siregar; Chan Siow Tian; Chang Seng Loong; Andre Wijaya Yamaputra; Sara Wahbeh (AIBPM Publisher, 2020)
This research aims to explore the internationalization process of PT.Indofood Sukses Makmur Tbk. To know how the strategies deployed by the company compete in the international market as well as suggest potential internationalization method for PT.Indofood Sukses to pursue for more internationally existence. In this research the author used secondary data, such as previous journal and report issued by the company. The conclusion of this research is that the key of success from PT.Indofood Sukses Makmur Tbk, is the mix marketing strategy and also their cooperation with multi-national companies. Their cooperation with other multi-national companies also will help the company to avoid being collapsed and instead growing steadily in the local market and international market as well. For that reason the author will try to analyse the strategies deployed by PT.Indofood Sukses Makmur